Bose-Einstein condensation in dilute gases - Pethick, Christopher (Cambridge, 2008)
Pethick and Smith provide a unified introduction to the physics of ultracold atomic Bose and Fermi gases for students, experimentalists and theorists alike. This book explains the phenomena in ultracold gases from basic principles, without assuming a detailed knowledge of atomic, condensed matter, and nuclear physics. This book provides chapters to cover the statistical physics of trapped gases, atomic properties, cooling and trapping atoms, interatomic interactions, structure of trapped condensates, collective modes, rotating condensates, superfluidity, interference phenomena, and trapped Fermi gases. Problems are included at the end of each chapter.